The equations of the hyperbola are
![y=\pm(b)/(a)(x-h)+k](https://img.qammunity.org/2023/formulas/mathematics/college/kgk7sxdlh3pm81n2dzbk237ftra5bi33l8.png)
(h, k) are the center of it
(h + a, k), (h - a, k) are the vertices
(h + c, k), (h - c, k) are the foci
From the graph, we can see the vertices are (-3, 3) and (3, 3), then
![\begin{gathered} h+a=3\rightarrow(1) \\ k=3 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/azseor7fek2ty30v9ecyaac4nr4160hbwn.png)
The foci are (-5, 3) and (5, 3), then
![h+c=5\rightarrow(2)](https://img.qammunity.org/2023/formulas/mathematics/college/p1s8wyk50dauznuxcb71tkkewwpigyjob9.png)
From the graph, we can see the center is the midpoint of the line joining the foci, then the center is (0, 3), then
h = 0
k = 3
Substitute the value of h in (1) and (2) to find a and c
![\begin{gathered} 0+a=3 \\ a=3 \\ 0+c=5 \\ c=5 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/m7m3ua97gd1g73wzhr4cb8xr4enqmvxr45.png)
Use the relation
![\begin{gathered} c^2=a^2+b^2 \\ b^2=c^2-a^2 \\ b^2=5^2-3^2 \\ b^2=25-9=16 \\ b=\pm4 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/k9lwfdt0nvg1d2unglv6fx7z4orclj2giq.png)
Now, substitute the values of a, b, h, k in the equations of the asymptote above
![\begin{gathered} y=(4)/(3)(x-0)+3 \\ y=(4)/(3)x+3 \\ y-3=(4)/(3)x\rightarrow(1st) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/ykew9o7v9avqxzid43vdb2rawjxohrixwr.png)
![\begin{gathered} y=-(4)/(3)x+3 \\ y-3=-(4)/(3)x \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/xc4cp1as6ig3bpgkrteufk8a8gbm134tw1.png)
The correct answer is A (1st equation of asymptote)